2009
DOI: 10.1590/s0124-00642009000100013
|View full text |Cite
|
Sign up to set email alerts
|

O Contexto Organizacional e a Experiência de Estress: uma Perspectiva Integrativa

Abstract: RESUMO@@@@@@@@@@@@@@@@ @@@@@@@@@@@@@@@@@@@ @@@@@@@@@@@@@@@@@@@-conciliar, até o atual papado, tendo obrigatoriamente como chave de concretização e manutenção das mudanças propostas por Francisco a consideração da com-preensão do dado da experiência humana, cristã e não cristã no desenvolvimento PALAVRAS CHAVES ABSTRACT: Historically, theology goes through various forms and it is directly @@@@@@@@@@@@@@@@@@ a practical historical perspective, the hermeneutic changes from the beginning of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
2
11
0
19
Order By: Relevance
“…The different roles, the lack of control and the absence of support from leadings to perform the job have been indicated as work features that influence on the stress occurrence and/or reduce the well-being of workers [15] .…”
Section: Discumentioning
confidence: 99%
See 1 more Smart Citation
“…The different roles, the lack of control and the absence of support from leadings to perform the job have been indicated as work features that influence on the stress occurrence and/or reduce the well-being of workers [15] .…”
Section: Discumentioning
confidence: 99%
“…These relationships are characterized for increasing of unemployment rates, restructuring of public and private sectors, decreasing of organization size, reducing of workers number, numeric increasing of people on temporary contracts and reducing of benefits to workers [15] . About this, researchers found that carrying health treatment, duration of employment, and occurrence and number of work absences were variables significantly associated to presenteeism among hospital nurses [15,16] . When the diseases related to presenteeism were analyzed among 296 hospital nurses from Portugal, the researchers observed that lumbar pain, respiratory infections, migraine and stress were the main causes of presenteeism [16] .…”
mentioning
confidence: 99%
“…professions may have different stressors elements that can trigger stress 29 and, in its chronicity, Burnout. One might think about this result in terms of professional formation, qualifications and expectations in the relationships with the customers.…”
Section: Discussionmentioning
confidence: 99%
“…Laranjeira 16 destaca, também, o problema do presenteísmo. Embora o trabalho docente tenha sofrido alterações ao longo do tempo, o professor não teve condições de criar meios para se adaptar às mudanças, levando ao surgimento de desequilíbrios na estrutura corporal.…”
Section: Souza Jc Costa Dsunclassified